Fungi Causing Leaf Spot Diseases of Soyabean: Their Epidemiology and Integrated Management Strategies - Borah, Munmi; Deb, Bishakha (International Journal of Economic Plants, 2022)
Majority of the leaf spot diseases on soybean crop is caused by different pathogenic fungi. Under favourable conditions and severe infection, it may result in heavy defoliation. It decreases the production efficiency of the crop by reducing the surface area available on leaves for photosynthesis. With less photosynthetic activity, the yield may be reduced significantly. Thus, making it a production constraint by reducing the economic viability of the infected soybean crop. Cercospora leaf spot, Target leaf spot, Alternaria leaf spot, Brown Spot, Phyllosticta leaf spot are the major leaf spots caused due to fungus in the soybean crop worldwide. In this review, we are discussing about economic importance, symptomatology, causal organism, disease cycle, epidemiology and integrated management of leaf spots caused due to fungal infection in the soybean crop.